Tinjauan Pustaka Perkembangan Sistem Monitoring Jaringan Berbasis Open Source: Studi Kasus Zabbix dan Uptime Kuma - Siti Aisyah Aliyah; Yulindon Yulindon (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The increasing complexity of network infrastructure requires monitoring systems capable of maintaining service availability and detecting disruptions quickly. Various open-source network monitoring platforms have been widely adopted, including Zabbix and Uptime Kuma. This study aims to analyze the development and characteristics of these two platforms through a literature review approach. Research data were collected from relevant scientific journal articles published between 2022 and 2026. The analysis was conducted by comparing several aspects, including monitoring mechanisms, feature capabilities, implementation complexity, and notification systems provided by each platform. The results indicate that Zabbix offers more comprehensive monitoring capabilities by providing real-time monitoring of network and server resources as well as historical performance analysis. In contrast, Uptime Kuma provides easier deployment, lower resource consumption, and effective service availability monitoring with real-time notification support. The development of open-source network monitoring systems demonstrates a trend toward solutions that are more flexible, easier to implement, and more responsive to network failures. The findings of this study are expected to serve as a reference for network administrators in selecting monitoring platforms that best suit their operational requirements and infrastructure characteristics.